Intercultural Communication Competence and Loneliness Among Out-Of-Town Students from Central Kalimantan - Ellia, Seth Kenan; Rahayu, Maria Nugraheni Mardi (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Out-of-town students from Central Kalimantan in the Special Region of Yogyakarta  and Central Java face challenges in adapting, becoming independent, and dealing with socio-economic difficulties, as well as experiencing a phenomenon of loneliness. This study explores the relationship between intercultural communication competence and their level of loneliness. The study uses a quantitative method with a correlational design and collects data through an online survey using a questionnaire that measures intercultural communication competence with the Intercultural Effectiveness Scale (IES) (α = 0.867) and level of loneliness with the UCLA Loneliness Scale (Version 3) (α = 0.925). The survey involved 235 overseas students from Central Kalimantan aged 18 to 24 years studying at various universities in DIY and Central Java, using the snowball sampling technique. Data analysis was performed using SPSS version 23 with tests for normality, linearity assumptions, and hypothesis testing with Pearson correlation. The analysis results show a significant negative relationship between intercultural communication competence and level of loneliness (r=−0.795; p=0.000), indicating that the higher the intercultural communication competence, the lower the level of loneliness felt by students. This study emphasizes the importance of developing intercultural communication competence in reducing the level of loneliness in ouf-of-town students.Mahasiswa rantau asal Kalimantan Tengah di Daerah Istimewa Yogyakarta (DIY) dan Jawa Tengah menghadapi tantangan dalam penyesuaian diri, mandiri, dan kesulitan sosial-ekonomi, serta terjadi fenomena kesepian sehingga penelitian ini mengeksplorasi hubungan antara kompetensi komunikasi lintas budaya dengan tingkat kesepian mereka. Penelitian ini menggunakan metode kuantitatif dengan desain korelasional dan mengumpulkan data melalui survei daring menggunakan kuesioner yang mengukur kompetensi komunikasi lintas budaya dengan skala Intercultural Effectiveness Scale (IES) (α = 0,867) dan tingkat kesepian dengan skala UCLA Loneliness (Version 3) (α = 0,925), melibatkan 235 mahasiswa rantau asal Kalimantan Tengah yang berusia 18 sampai 24 tahun dan menempuh pendidikan di berbagai universitas di DIY dan Jawa Tengah, dengan teknik snowball sampling, analisis data dilakukan menggunakan SPSS versi 23 dengan uji asumsi normalitas, dan linearitas, serta uji hipotesis korelasi Pearson. Hasil analisis menunjukkan adanya hubungan negatif yang signifikan antara kompetensi komunikasi lintas budaya dengan tingkat kesepian (r=−0,795; p=0,000), menunjukkan bahwa semakin tinggi kompetensi komunikasi lintas budaya, semakin rendah tingkat kesepian yang dirasakan oleh mahasiswa. Penelitian ini menegaskan pentingnya pengembangan kompetensi komunikasi lintas budaya dalam mengurangi tingkat kesepian pada mahasiswa rantau.